Observation of collectivity enhanced magnetoassociation of 6Li in the quantum degenerate regime - Vineetha Naniyil; Yijia Zhou; Guy Simmonds; Nathan Cooper; Weibin Li; Lucia Hackermüller (New Journal of Physics, 2022)
The association process of Feshbach molecules is well described by a Landau–Zener (LZ) transition above the Fermi temperature, such that two-body physics dominates the dynamics. However, using ^6 Li atoms and the associated Feshbach resonance at B _r = 834.1 G, we observe an enhancement of the atom–molecule coupling as the fermionic atoms reach degeneracy, demonstrating the importance of many-body coherence not captured by the conventional LZ model. In the experiment, we apply a linear association ramp ranging from adiabatic to non-equilibrium molecule association for various temperatures. We develop a theoretical model that explains the temperature dependence of the atom–molecule coupling. Furthermore, we characterize this dependence experimentally and extract the atom–molecule coupling coefficient as a function of temperature, finding qualitative agreement between our model and experimental results. In addition, we simulate the dynamics of molecular association during a nonlinear field ramp. We find that, in the non-equilibrium regime, molecular association efficiency can be enhanced by sweeping the magnetic field cubically with time. Accurate measurement of the atom–molecule coupling coefficient is important for both theoretical and experimental studies of molecular association and many-body collective dynamics.